Institutional readiness factors and the adoption of remote learning platforms among university stakeholders in Nigeria during COVID-19 pandemic (2021)
The advent of COVID-19 pandemic has brought the new normal, not only in social interactions but also in teaching-learning activities. It caused the sudden change by most education institutions to remote learning platforms as a result of state configuration policies that prohibited social gathering and enforced social distancing. Lack of empirical findings on responses of higher education stakeholders to the adoption of remote learning platforms during COVID-19 pandemic created an impetus to examine institutional readiness factors and the adoption of remote learning platforms among public and private universities’ stakeholders. This descriptive survey design used a total population of all academic staff of universities in the Southwest Nigeria. One hundred and sixty eight (168) participants were randomly sampled across states in the Southwest using a validated on-line instrument designed on “Google form” and which had a Cronbach Alpha coefficient of (r=0.70). Data collected was analysed using blinder Oaxaca decomposition procedure of Stata. The result revealed that the tendency to adopt the remote learning platform by both private (F(4, 41) =3.15, p<0.05) and public F(4, 113) =2.93, p<0.05) stakeholders was significant. The level of readiness of public institutions’ stakeholders in terms of facilities, training, self-efficacy and perceived usefulness of remote platforms was not significant while the self-efficacy of private stakeholders was significant (ß = .063, t =2.16, p<0.05). The result informed the need for more trainings and provision of facilities for optimum readiness for any future emergency like COVID-19 pandemic.